The Dynamics of Multigenre Literary Textual Shifts in Ayu Utami’s Saman: A Cognitive Poetics Perspective - Ahmad Rifai; Ismail Marzuki; Islam Ragab Abdelhamid Shehata3; Hani Agustina (E-Link Journal, 2025)
This study analyzes the shifts of text worlds in the novel Saman through Cognitive Poetics, particularly Text World Theory and the activation of mental schemata. With its multigenre character, ranging from poetic, documentary, erotic, and religious modes to light conversation and tragedy, Saman presents stylistic transitions that continually reshape the reader’s spatial, temporal, evaluative, and emotional orientations. The research employs a qualitative approach with units of analysis in the form of narrative fragments that mark genre transitions. The analysis involves close reading, text-world mapping, schema tracking, and the assessment of inter-genre coherence. The findings reveal three major cognitive strategies: the shift from phatic to evidential schemata in personal tragedy, the transition from embodied cognition to moral reasoning in erotic–religious passages, and the emergence of structured empathy in the move from poetic to documentary modes. This study fills a gap in previous research, which has rarely discussed the cognitive experience of Saman’s readers, while also highlighting the novel’s uniqueness as a multigenre text that demands high cognitive flexibility from its audience.